Keterkaitan Volume Prostat dengan Skor IPSS pada Penderita Benign Prostatic Hyperplasia (BPH) di RSU Haji Medan - Jihan Maghfira; Hasroni Fathurrahman; Aril Rizaldi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Benign prostatic hyperplasia (BPH) is a benign neoplasm characterized by hyperplasia in the periurethral area of the prostate. This condition often causes lower urinary tract symptoms (LUTS) that can interfere with daily activities although rarely life-threatening. Prostate volume is an important indicator to assess the severity, progressivity of the disease, as well as response to treatment. The International Prostate Symptom Score (IPSS) questionnaire is used to measure the severity of LUTS symptoms. This study aimed to evaluate the relationship between prostate volume and IPSS score in BPH patients at RSU Haji Medan. This study used a retrospective analytic observational design with a cross-sectional approach. Samples were selected based on inclusion and exclusion criteria, with data taken from BPH patients in the urology department of RSU Haji Medan during the period September to December. Analysis was performed using Spearman correlation test. Of the 93 samples, the highest incidence of BPH was found in the age group of 61-70 years (43.0%). Most prostate volume was in classification 1 (20-39 cc) with 53 people (57.0%), while the most frequent degree of symptoms was severe degree (high IPSS) with 39 people (41.9%). Spearman correlation test showed a significant association between prostate volume and IPSS score (p < 0.001), with a very strong positive correlation coefficient (r = 0.853), indicating a unidirectional relationship. Prostate volume has a significant relationship with IPSS score in patients with Benign Prostatic Hyperplasia (BPH). This finding underscores the importance of prostate volume measurement in assessing symptom severity and determining treatment strategies.